Detection of genetic relations between species in the genus Prunus L. when using them in breeding of stone fruit crops - G. V. Eremin (Труды по прикладной ботанике, генетике и селекции)
Research conducted at Krymsk Experiment Breeding Station of VIR on the gene pools of stone fruit plants and genomic analysis of the genetic collection of interspecific hybrids within the genus Prunus L. disclosed differences in the degree of incompatibility among the studied species. There are four levels in the manifestation of this indicator in hybrid F1 families:-    the first level: some hybrids are normally prolific. This is characteristic of hybrids produced by the species of one section at the same level of ploidy;-    the second level: fertility of hybrids is reduced, but some of them produce fruits and partially fertile pollen. This level is typical for hybrids from crosses between species at the intersection level within one subgenus;-    the third level: F1 hybrids are infertile, but in some of them partial viability of pollen is observed. This effect is manifested by hybrids between the species of the subgenus Prunophora, and the species of the subgenus Amygdalus;-    the fourth level: no hybrids are produced.Genomic morphological markers were also used in genomic analysis. Based on the information obtained in the process of genomic analysis, a number of changes are proposed in the system of the genus Prunus.It is proposed to transfer the species of the sections Microcerasus (subgenus Cerasus) and Amygdalopsis (subgenus Amygdalus) to the subgenus Prunophora, since they manifest the first level of incompatibility with the species of other sections in the subgenus Prunophora. The species P. maackii should be included in the Cerasus section of the subgenus Cerasus together with two other tetraploid species of cherry: P. vulgaris (P. cerasus) and P. fruticosa, as it is crossed with latter two showing the first level of incompatibility, and all these species have a common diploid ancestor: P. canescens. The species P. microcarpa which has marker traits typical for the species in the Spiraeopsis subsection of the Microcerasus section should be relocated from the subsection Microcerasus (Amygdalocerasus) to the subsection Spiraeopsis.